Analysis of Competency GAPs among Computer and Network Engineering (TKJ) Students in Relation to Industry Needs and Their Implications for Learning Technology Design - Ashabul Taufik; Kamal; Nur Alamsyah (Yayasan Ahmar Cendekia Indonesia, 2026)
This study aims to analyze the competency GAP of Computer and Network Engineering (TKJ) students in relation to industry demands and to formulate its implications for instructional technology design. This study employs a mixed methods approach with an explanatory sequential design involving 31 twelfth-grade TKJ students who have completed their industrial internship (Praktik Kerja Lapangan/PKL). Quantitative data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and GAP analysis, while qualitative data were obtained from open-ended responses and analyzed using thematic analysis. The results show that TKJ learning has provided a strong foundation of basic competencies, particularly in preparing students for industrial internships and initial job readiness. However, competency GAPs remain in the integration of up-to-date industrial technologies and the depth of troubleshooting practices aligned with industry standards. The GAP analysis reveals that the highest GAPs occur in the discussion of current technologies (1.48) and troubleshooting skills based on industry standards (1.45). The findings of this study indicate that integrating quantitative GAP analysis with qualitative reflections from internship experiences provides a comprehensive empirical basis for developing adaptive, practice-based, and industry-aligned instructional technology design.